2007
DOI: 10.1063/1.2745814
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of pure electron plasmas in the Columbia Non-neutral Torus

Abstract: The Columbia Non-neutral Torus ͑CNT͒ ͓T. S. Pedersen, J. P. Kremer, R. G. Lefrancois, Q. Marksteiner, N. Pomphrey, W. Reiersen, F. Dahlgreen, and X. Sarasola, Fusion Sci. Technol. 50, 372 ͑2006͔͒ is a stellarator used to study non-neutral plasmas confined on magnetic surfaces. A detailed experimental study of confinement of pure electron plasmas in CNT is described here. Electrons are introduced into the magnetic surfaces by placing a biased thermionic emitter on the magnetic axis. As reported previously, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…The electric field around the rod that pushes electrons away from the rod also creates an E × B drift across the magnetic surfaces (radially) and allows electrons to escape. The observed rod-driven transport is in good agreement with a model of this process [16].…”
Section: Understanding and Improving Confinementsupporting
confidence: 74%
“…The electric field around the rod that pushes electrons away from the rod also creates an E × B drift across the magnetic surfaces (radially) and allows electrons to escape. The observed rod-driven transport is in good agreement with a model of this process [16].…”
Section: Understanding and Improving Confinementsupporting
confidence: 74%
“…The anisotropic tensor would lead to force terms, some along B, usually neglected both in the electron fluid equation and the ideal MHD Ohm's law. Numerical simulations show that > 50% of the electrons are on magnetically trapped orbits, and that there are complicated loss structures in phase space in CNT [31], also consistent with experimental findings [17,32]. The dominant collisional process in these plasmas is electron-neutral collisions, and they are quite rare [17] (ν en ≈ 500 s −1 for η = 0.3).…”
Section: Discussionsupporting
confidence: 76%
“…The magnitude and approximate 1/p n scaling for the confinement time for helium dominated experiments is consistent with measurements of the transport in steady state experiments with helium. The 1/p n scaling is well understood as being electron-neutral collision driven transport and was also observed for nitrogen dominated steady state experiments [10,14].…”
Section: Ion Accumulation Cause Of Fast Collapsementioning
confidence: 60%
“…Thus the Debye length is much smaller than the 15 cm minor radius. It was established early on that the presence of internal structures (ceramic rods) caused significant transport [10,14], but it was also found that these rods prevented continuous ion accumulation, and that the ion content would therefore reach a steady state value. At low neutral pressures (p n < 5 × 10 −9 Torr) the ion content would be less than 1 % [15].…”
Section: The Cnt Experimentsmentioning
confidence: 99%
See 1 more Smart Citation